Land reclamation & soil improvement using dredged slurry as fill - Lam, Kok Pang (2018)
Dredged seabed materials are proposed as an alternative reclamation fill for sand depleted cities. Hydraulic dredging and infilling are identified as the most efficient and cost-effective ways to place large quantities of dredged materials at shallow depth when dump barges cannot be used. However, the intermixing of the dredged materials with seawater in hydraulic dredging will destroy its soil fabrics forming slurry with poor engineering properties. These will bring about many site challenges affecting project costs, schedule and meeting the specified technical requirements. A series of laboratory model tests and two field trials were carried out. Laboratory model tests were carried out to examine the behaviors of natural and flocculants treated sedimentation process of dredged slurries. Findings showed that the inclusion of flocculents although could bring faster settling by forming larger focs in the dredged slurry suspension, they also modified the sediments fabrics causing larger consolidations to occur. Laboratory model tests were also carried out to evaluate the performance of vacuum preloading techniques to improve different types of marine clays with very high water content. The model tests concluded that vacuum preloading technqiues are effective in enhancing the engineering properties of different high water-content marine clay samples. However, the degree of improvement in the marine clay samples were observed to reduce with increasing distance from the prefabricated drains transmitting the vacuum. In the first field trial, a combined membraneless vacuum and embankment preload field trial was carried out over a newly reclaimed land. Site observations concluded that the performance of this technique were largely affected by vacuum pump’s reliability and the accuracy of the soil profiles obtained. In the second field trial, hydraulic dredged slurries were used as the main infill. Key site challenges in using dredged slurries as infill were described and illustrated. A new land reclamation method of applying vacuum through horizontally placed prefabricated horizontal drains was proposed. Laboratory studies and numerical analysis were carried out to examine the feasibilities of this method. The results showed positive outcomes in addressing the key site challenges while improving operational productivity and increase infill capacity when dredged seabed slurry are used as reclamation infill. Several recommendations are proposed for further study to develop the new land reclamation method.